2018
DOI: 10.1002/jum.14840
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Imaging in the Demonstration of Common Shear Wave Artifacts

Abstract: In this article, we describe our experience with shear wave propagation imaging (SWPI) as an adjunct to 2‐dimensional (2D) shear wave elastography (SWE) in a cohort of patients being evaluated for diffuse liver disease. Two‐dimensional SWE has been extensively studied in previous publications; however, 2D SWE using propagation images has not been widely described in the literature to date. We observed that when certain artifacts occurred on the color elastograms, highly characteristic changes to shear wave pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The most consistent estimates are generally obtained near the focus zone of the ARFI pulse, where the largest displacements is generated by the push pulses [22]. A detailed analysis of all the artifacts is out of the scope of this review article and can be found elsewhere [22][23][24].…”
Section: Region Of Interestmentioning
confidence: 95%
“…The most consistent estimates are generally obtained near the focus zone of the ARFI pulse, where the largest displacements is generated by the push pulses [22]. A detailed analysis of all the artifacts is out of the scope of this review article and can be found elsewhere [22][23][24].…”
Section: Region Of Interestmentioning
confidence: 95%
“…Similar to conventional sonography, limitations of 2D-SWE revolve around motion artifacts, depth of signal penetration, and thickness of subcutaneous fat. 31,32 Most of the available research into liver tumor stiffness has relied on pSWE, where the operator uses B-mode to select the ROI in a single focal location. Thus, measurements acquired using pSWE do not often encompass the entire tumor and cannot account for anatomic boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…There are three 2D-SWE techniques in use: (1) 1-dimensional transient elastography, (2) point shear wave elastography (pSWE), and (3) 2D-SWE. Similar to conventional sonography, limitations of 2D-SWE revolve around motion artifacts, depth of signal penetration, and thickness of subcutaneous fat 31,32 . Most of the available research into liver tumor stiffness has relied on pSWE, where the operator uses B-mode to select the ROI in a single focal location.…”
Section: Discussionmentioning
confidence: 99%
“…26 Fifth, the placement of the ROI in the center of the image and at proper depth may help to avoid effects of shadowing (from lung, ribs) and visible hepatic vessels on measuring ultrasound parameters of the liver. 17,27 An important notion was that multiparametric ultrasound was feasible in differenting normal and steatotic livers whereas serum biomarkers were not in the study. SWV representing liver stiffness and NLV indicating difference between measured liver echo amplitude (intensity) and the theoretical echo amplitude remarkably decrease in hepatic steatosis, whereas SWD representing liver viscosity, ATI for liver attenuation, and L/K ratio as difference in echo intensity between the liver and kidney cortex significantly increase in hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, keeping the emission sound beam perpendicular to the liver capsule can decrease anisotropy artifacts 26 . Fifth, the placement of the ROI in the center of the image and at proper depth may help to avoid effects of shadowing (from lung, ribs) and visible hepatic vessels on measuring ultrasound parameters of the liver 17,27 …”
Section: Discussionmentioning
confidence: 99%